Crop productivity and potential - Berhane, Guush; Minten, Bart; Bachewe, Fantu Nisrane; Koru, Bethlehem (International Food Policy Research Institute, 2020)
Chapter 3, “Crop Productivity and Potential,” documents and explains the causal factors for the rapid expansion in crop production in Ethiopia (official estimates show an increase in production of grain crops from 16.1 million metric tons to 30.6 million metric tons from 2007/2008 to 2017/2018). Using data on input use (such as land, improved seeds, fertilizer, and agricultural extension services), the authors estimate the combined effect of increased inputs. The residual, then, is an estimate of the gains in total factor productivity. Further rapid gains in yields seem less likely, though, given the high levels of input use already achieved. They illustrate some of the challenges in crop production, linked to the research and extension system, the limited access to irrigation, and the seed sector.